Does an isometric neck strengthening intervention reduce skull sway after impact in female athletes? A pilot study - Kadlec, D.; Snyder, L. (Sport Performance & Science Reports, 2018)
Understanding the e cacy of distinct training interventions on the likelihood of injuries is crucial for the practitioner and athlete alike. One often underrated injury is a concussion, which has shown to increase the odds of sustaining a subsequent musculoskeletal injury.(1) Additionally, severe cognitive, psychological and structural pathologies have been reported after a diagnosed concussion.(2) Concussions occur after an external force has been applied to the head, neck or elsewhere on the body, which cause a sudden acceleration or deceleration of the head resulting in a collision between the brain and the skull.(3) Therefore, strategies to reduce head accelerations or decelerations after an impact might minimize the risk of sustaining a concussion. Athletes with a higher isometric neck strength exhibit a decreased acceleration of the skull after an impact (4) and have a decreased likelihood of sustaining a concussion.(5) Further, speci c neck training interventions have shown to decrease the prevalence of concussions in male athletes.(6) However, female athletes are thought to Fig. 1. Visual representation of the test set-up. be at a higher risk, because they display lower maximal voluntary isometric contraction (MVIC) values as well as have lower neck muscle volumes than male athletes.(7) There is a lack of data about the e cacy of an intervention of neck strengthening on skull kinematics after an impact in female athletes. Aim. The purpose of this study is to investigate whether an isometric neck strengthening program decreases peak acceleration of the skull after an impact in female athletes.